Feasibility of targeted axillary dissection for de-escalation of surgical treatment after neoadjuvant chemotherapy in breast cancer. (September 2022) - Aragón-Sánchez, Sofía; Ciruelos-Gil, Eva; López-Marín, Laura; Galindo, Alberto; Tabuenca-Mateos, María José; Jiménez-Arranz, Sara; Colmenero-Hernández, María; Oliver-Pérez, María Reyes
Abstract: Background: Targeted axillary dissection, which combines sentinel lymph node biopsy with removal of the proven involved node noted during the staging process, has been shown to improve axillary staging and decrease false negative rates after neoadjuvant chemotherapy in patients with breast cancer. Objective(s): The main goal of this study was to assess the ability to identify and remove the clipped node and the false negative rate of targeted axillary dissection. Methods: We performed a prospective study among patients with biopsy-confirmed nodal metastases who received neoadjuvant chemotherapy. A clip was placed on the sample node prior systemic therapy. After neoadjuvant chemotherapy, all patients underwent sentinel lymph node biopsy (dual tracer), localization and excision of the clipped node and axillary lymph node dissection. The clipped node was preoperatively localized in all cases placing an iodine-125 seed guided by ultrasound. The pathology of the sentinel nodes and clipped node was compared with other nodes. Results: A total of 455 patients with invasive breast cancer were studied. Of the 148 patients with NAC, 32 met the eligibility criteria and were enrolled in the study. Mean age at diagnosis was 52.3 years. Systematic lymphadenectomy was performed in all patients, with an average of 14.3 lymph nodes removed. Detection rate of the clipped node alone was 96.9%, and 100% for targeted axillary dissection. Ability of clipped node alone to predict nodal status showed a FNR of 10, 5% while SLNB alone performed by dual tracer and targeted axillary dissection, showed FNRs of 5.3% and 5.0%, respectively. Sentinel lymph nodes matched clipped node in 23 patients (74.2%). Conclusion (s): In node positive breast cancer patients, targeted axillary dissection is a reliably approach for axillary staging after neoadjuvant chemotherapy. The preoperative location of the clipped node is mandatory to increase the detection rate and optimize the results of the technique. Highlights: Targeted axillary dissection is a reliably approach for axillary staging after neoadjuvant chemotherapy. Detection rate of targeted axillary dissection is 100% when a preoperative location of the clipped node is performed. The clipped node provides additional information for axillary staging, as it does not match with the sentinel node in 25.8% of patients.